Ethnozoological knowledge of traditional fishing villages about the anadromous sea lamprey (Petromyzon marinus) in the Minho river, Portugal - Heitor Oliveira Braga; Mário Jorge Pereira; Fernando Morgado; Amadeu M. V. M. Soares; Ulisses Miranda Azeiteiro (BMC, 2019)
Abstract Background Sea lamprey (Petromyzon marinus) is a diadromous fish compromised by various stressors, which can lead to population decline and the urgency of stronger conservation regulation. In the absence of documentation of direct knowledge of local populations, a broader zoological and ecological understanding of sea lamprey fishing has become vital for the preservation of traditional practices and conservation of this migratory fish. To this purpose, we collected data from the P. marinus about the artisanal fisheries profile, folk taxonomy, habitat, reproduction, migration, and displacement using a low-cost methodology, through ethnobiology tools, in the four riverine fishing villages in Portugal. Methods A total of 40 semi-structured interviews were carried out during the winter of 2019 in crucial fishing villages in the Minho river. Fishers were selected by random sampling and the snowball technique when appropriate. Interviews applied contained four parts (fisher's profile, projective test, knowledge about fishing, and ethnozoological knowledge about the sea lamprey). Informal knowledge was analyzed following an emic-etic approach and the set-theoretical Union of all individual competences. The Code of Ethics of the International Society of Ethnobiology (ISE) was the main parameter for the conduction of this ethnozoological research and related activities in the Cooperminho project. Results This first ethnobiological study of the sea lamprey (Petromyzon marinus) in Portugal showed a sample of predominantly male fishers, averaging 57.13 years old, and average fishing experience of 37.18 years. The average income of fishers is about 688.28 Euros, and the level of education was predominantly basic. Data from artisanal fisheries showed the time and frequency of fishing, the characterization of fishing boats, and general information on catching lamprey in the Minho river. Three new folk names were attributed to P. marinus. Fishers mentioned sites with rock fragments and sandy bottoms and depth ranges ranging from 0 to 8 m as likely sea lamprey habitats. The villages of Monção and Melgaço are the last areas of the river where you could spot sea lamprey, as well as the last probable spawning grounds for this fish in the Minho river. The hydroelectric dams and predatory fisheries were considered the main obstacles to the migration of sea lamprey. Finally, local fishers also shared the lamprey migration season to feed and spawn. Conclusions Fishers shared a vast informal knowledge of sea lamprey zoology and ecology typical of anadromous species of the Petromyzontidae family, in the central traditional Portuguese communities on the Minho river. This fisher's knowledge becomes essential to preserve cultural practices of the sea lamprey, which is currently highly susceptible to anthropogenic pressures. Given the real warning of population extinction in the Portuguese rivers (such as the Minho river) and a similar trend in Spanish territory, ethnozoological studies of sea lamprey in Spanish fishing communities may support our findings. Also, this study may assist in the adaptive participatory management of these anadromous fish, as well as in documentation of local ecological knowledge (LEK) and centuries-old fishing practices that are also vulnerable in modern times on the international frontier Minho river.